First observation of the decay B*s2(5840)0→B*+K− and studies of excited B0s mesons - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
The properties of the orbitally excited (L=1) B0s states are studied by using 1.0 fb−1 of pp collisions at √s=7 TeV collected with the LHCb detector. The first observation of the B∗s2(5840)0 meson decaying to B*+K− is reported, and the corresponding branching fraction measured relative to the B+K− decay mode. The Bs1(5830)0→B*+K− decay is observed as well. The width of the B∗s2(5840)0 state is measured for the first time, and the masses of the two states are determined with the highest precision to date. The observation of the B∗s2(5840)0→B*+K− decay favors the spin-parity assignment JP=2+ for the B∗s2(5840)0 meson. In addition, the most precise measurement of the mass difference m(B*+)−m(B+)=45.01±0.30(stat)±0.23(syst) MeV/c2 is obtained.
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 596
Im Titel sind "0", "+" und "-" hochgestellt und "s2" und "s" tiefgestellt
Gesehen am 23.03.2021